Pengaruh Environmental Concern dan Perceived Environmental Knowledge Terhadap Niat Beli Hijau Melalui Environmental Attitude Sebagai Variabel Mediasi (Studi pada Calon Konsumen Refill Station The Body Shop) - Alamsyah, Ali; Artanti, Yessy (Jurnal Ilmu Manajemen, 2023)
Sustainability on business is one thing that we can do to save the earth. Otherwise there is still so many company that doesnt do the sustainability on their business. This study aims to determine the effect of environmental concern and perceived environmental knowledge on green purchasing intentions through environmental attitude as a mediating variable. This study used a purposive sampling method, using 100 respondents. Using a path analysis model with AMOS software. The results of this study indicate that there is an influence between perceived environmental knowledge and environmental attitude towards green purchasing intentions, but this study did not find any influence from environmental concerns on green purchasing intentions because consumption patterns of green products have not yet been formed. This research is useful for researchers and beauty brands in Indonesia, especially Refill Station The Body Shop, to pay attention and care about the importance of perceived environmental knowledge and environmental attitude for consumers.